Temperature and dehydration effects on respiratory and cutaneous water flux in the terrestrial toad, Rhinella schneideri (Anura, Bufonidae) - Castro, Luis Miguel Senzano [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
As ectotherms, amphibians may experience wide fluctuations in body temperature and, due to their high skin permeability, terrestrial species face a constant risk of desiccation. These two variables (temperature and dehydration) are centrally relevant for water balance regulation because they directly affect water flux through the integument, i.e. skin evaporative water loss (EWLSkin) and water uptake (WU). In addition, as nearly all anurans are lung breathers, the respiratory water loss (EWLResp) will add to EWLSkin. Although the contribution of EWLResp to total EWL (EWLTotal) is generally assumed to be negligible, the partitioning between EWLSkin and EWLResp varies among species and is affected by temperature and dehydration. Therefore, we investigated the combined effects of temperature and dehydration on the rates of EWL through the skin and the lungs of the terrestrial toad, Rhinella schneideri. Subsequently, we evaluated how water uptake (WU) through the pelvis skin was affected by temperature and dehydration. To this aim, we measured rates of EWLTotal and EWLSkin in intact and masked adult toads at 15, 25 and 35 oC under fully hydrated condition and dehydrated until they have lost 10% and 20% of their initial body mass. Masked toads were able to breath normally during the measurement of EWLSkin; EWLResp was calculated as EWLTotal minus EWLSkin. Rates of EWL were also determined using biophysical agar models of R. schneideri specimens, which allowed the estimation of skin resistance (Rs) to evaporation. WU rates were determined by measuring body mass gain against rehydration time of toads placed on a thin film of water. EWLSkin and EWLResp increased with temperature, however, this effect was much more pronounced for EWLResp than for EWLSkin and, as a result, the partitioning between cutaneous and respiratory water loss was significantly altered with temperature. Indeed, the contribution of EWLResp to EWLTotal increased from 2.44% at 15 oC to 8.1% at 35 oC. This result may be attributed to a limited capacity for EWLSkin regulation combined with a temperature induced increment in pulmonary ventilation resulting from the elevation in metabolic rate with temperature. The contribution of EWLSkin to EWLTotal decreased with dehydration which may be related to a loss in skin water content and the subsequent compression of cell layers, which limit water efflux to the environment. Therefore, the relative contribution of EWLResp augmented with temperature and dehydration accompanied by the corresponding decrease in the relative contribution of EWLSkin. Rates of WU increased with dehydration but not with temperature, which indicate the central role of the osmotic gradient in driving water flow through the anuran skin.

Como animais ectotérmicos, os anfíbios experimentam longas flutuações na temperatura corpórea e, devido à sua alta permeabilidade cutânea, eles também enfrentam o risco constante da dessecação. Essas duas variáveis (temperatura e desidratação) são muito relevantes no contexto do balanço hídrico dado que elas afetam diretamente o fluxo de água através da pele, ou seja, a perda evaporativa de água (PEAPele) e a absorção de água (RE). Além disso, dado que a maioria dos anuros possuem respiração pulmonar, a perda de água respiratória (PEAResp) irá se adicionar à cutânea. Embora a contribuição da PEAResp para a perda de água total (PEATotal) seja geralmente considerada insignificante, a divisão entre PEAPele e PEAResp varia de acordo com as espécies e é afetada pela temperatura e desidratação. Portanto, nós investigamos os efeitos combinados da temperatura e desidratação nas taxas de PEA através da pele e pulmões no sapo terrestre, Rhinella schneideri. Posteriormente, avaliamos como a absorção de água através da pele ventral (RE) foi afetada pela temperatura e desidratação. Para isso, medimos as taxas de PEATotal e PEAPele em sapos adultos intactos e mascarados à 15, 25 e 35 oC e desidratados até perderem 10% e 20% da massa corpórea inicial. Os sapos mascarados foram capazes de respirar normalmente durante a medição da PEAPele; PEAResp foi calculado como PEATotal menos PEAPele. As taxas de perda de agua também foram determinadas usando modelos de ágar de espécimes de R. schneideri, o que permitiu a estimativa da resistência da pele (RP) à evaporação. As taxas de RE foram determinadas medindo o ganho de massa corpórea durante o tempo de reidratação dos sapos colocados sobre uma fina camada de água. PEAPele e PEAResp aumentaram com a temperatura, no entanto, este efeito foi muito mais marcado para a PEAResp do que para a PEAPele e, como resultado, a divisão entre a perda de água cutânea e respiratória foi significativamente alterada com a temperatura. De fato, a contribuição da PEAResp para a PEATotal aumentou de 2,44% a 15 oC para 8,1% aos 35 oC. Este resultado pode ser atribuído a uma capacidade limitada para a regulação da PEAPele, combinada com um aumento na ventilação pulmonar induzido pela temperatura devido à elevação na taxa metabólica. A contribuição de PEAPele para a PEATotal diminuiu com a desidratação, o que pode estar relacionado à perda de conteúdo de água da pele e a subsequente compressão das camadas celulares, o que limita o fluxo de água para o ambiente. Portanto, a contribuição relativa da PEAResp aumentou com a temperatura e a desidratação, acompanhada da diminuição correspondente da contribuição relativa de PEAPele. As taxas de RE aumentaram com a vii desidratação, mas não com a temperatura, o que indica o papel central do gradiente osmótico na condução do fluxo de água através da pele.
Efeitos da temperatura e desidratação no fluxo de água respiratória e cutânea no sapo terrestre, Rhinella schneideri (Anura, Bufonidae)
Keywords: Anfíbio; Amphibians; Evaporative water loss; Skin resistance; Water uptake; Lung ventilation